2009
DOI: 10.1088/0022-3727/42/20/205005
|View full text |Cite
|
Sign up to set email alerts
|

A current-controlled, dynamic magnonic crystal

Abstract: We demonstrate a current-controlled, dynamic magnonic crystal. It consists of a ferrite film whose internal magnetic field exhibits a periodic, cosine-like variation. The field modulation is created by a direct current flowing through an array of parallel wires placed on top of a spin-wave waveguide. A single, pronounced rejection band in the spin-wave transmission characteristics is formed due to spinwave scattering from the inhomogeneous magnetic field. With increasing current the rejection band depth and it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
155
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(164 citation statements)
references
References 32 publications
2
155
0
7
Order By: Relevance
“…It is shown that the process is one of oscillatory inter-modal energy exchange. We explore the features of the effect experimentally using spin waves (magnetic excitations, the quanta of which are known as magnons [15,17]) in a dynamic magnonic crystal (DMC) [8,14,15], and show that results are consistent with a theoretical description of the coupling phenomenon which models the waves as interacting harmonic oscillators.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…It is shown that the process is one of oscillatory inter-modal energy exchange. We explore the features of the effect experimentally using spin waves (magnetic excitations, the quanta of which are known as magnons [15,17]) in a dynamic magnonic crystal (DMC) [8,14,15], and show that results are consistent with a theoretical description of the coupling phenomenon which models the waves as interacting harmonic oscillators.…”
mentioning
confidence: 82%
“…Such systems-which include optical photonic crystals [1][2][3][4][5][6][7] and magnetic magnonic crystals [8][9][10][11][12][13][14][15]-belong to the class of so-called metamaterials: synthetic media with properties derived from an engineered mesoscopic structure. The wave transmission spectra of artificial crystals typically include band gaps which arise as a result of resonant wave-lattice interactions analogous to the atomic-scale Bragg scattering phenomena observed in natural crystals [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The spin-wave dispersion relation depends on many parameters, such as the geometry of the spin-wave waveguide (film thickness and waveguide width), external magnetic field H ext , and saturation magnetization M S . In fact, all of these parameters have already been used to fabricate magnonic crystals [6][7][8]12,13,[18][19][20] : arrays of metallic stripes, etched grooves or antidots, biasing magnetic field or periodic variation of the saturation magnetization using ion implantation.However, all available methods for the fabrication of such spintronic devices result in spatially constant magnetic materials. J. Topp et al have shown that the parameters of magnetic materials can be changed locally after the rather time-consuming fabrication of the spintronic device 21 -but the functionality of the device stays the same.…”
mentioning
confidence: 99%
“…Wherein the frequency selectivity and waveguide properties of the device are achieved by creating a priority for wave propagating with certain k in magnonic crystals or SW confinements. [6][7][8] Extended in plane YIG films are grown by different techniques on gallium gadolinium substrates directly [9][10][11] or with copper interlayer. 12 In consequence, patterns of the required sizes are cut 13 or etched 14 from the film.…”
Section: Introductionmentioning
confidence: 99%